Revisiting interactions between polygalacturonases and polygalacturonase-inhibiting proteins and their effects on plant health: a review - Mallick, Pallavi; Singh, Dikchha; Choudhary, Prassan; Kolla, Varaprasad (Frontiers in Plant Science, 2025)
Polygalacturonases (PG) are recognized as key cell-wall-degrading enzymes in phytopathogenic fungi. Plants have a well-developed defense mechanism to counter invasive pathogens, yet such attacks harm the plants. The present review aims to understand the interactions of fungal polygalacturonases with their host invasions affecting plant health. The study also discusses in detail the structure–function relationships of PG interactions with their host counterparts. The role of PGIPs has been emphasized in correlation to algorithms designed to unravel plant microbe interactions involving PGs. With ever-changing environmental stress indicators, it becomes absolutely important to understand plant adaptations on a proteomic and metabolomic level. This would help plant disease diagnosticians in devising early warning or prediction systems for crop-specific protection based on PG–PGIP interactions.